Comparison of Titanium Elastic Nails (TEN) Vs Traction and Hip Spica Cast for Treatment of Femoral Shaft Fracture in Children Age 6-12 years. - Ghulam Rasool; Zafar Malik, M. Naeem Ashraf, Azhar, (Journal of Rawalpindi Medical College, 2013)
Background : To Compare titanium elastic nails (TEN) Vs traction and hip spica cast for treatment of femoral shaft fracture in children aged 6-12years. Methods: In this descriptive study, children (n=100), age group 6 to 12 years, with femoral fractures, were included. Patients were divided into two equal groups using randomization. Group A patients were treated with Titanium Elastic Nail (TEN) (n=49) and group B patients with traction and hip spica (n=51).Back slab was applied to all patients. For patients in the TEN group, the standard TEN technique was applied Majority of the patients underwent surgery within two days of their injury. Two Titanium Elastic Nails of identical diameter were used. Fractures were reduced using fluoroscopic guidance. Nails were inserted in retrograde/antegrade fashion according to fracture geometry. In retrograde elastic nailing, medial and lateral incisions above the physis were made. The nails were prebent sufficiently so that apex of the bowed nails rested at the same level on the fracture site to ensure a good equal recoil force. The nails were driven proximally so that both were divergent and the tips got anchored. Patients were mobilized without weight bearing on the fifth to seventh day postoperatively. Partial weight bearing was started at three weeks and full weight bearing by six to eight weeks. Patients in the spica cast group were treated with skin traction/ skeletal traction for about 3 weeks and then hip spica was applied. When sufficient callus consolidation had been achieved, one-and-a-half hip spica was applied . The cast was maintained for about 1-2 months depends on the age of patient. After cast removal, patients were referred for physical therapy. Results: Those treated with titanium elastic nail (TEN) had radiological union time 4-6 weeks and took a shorter time, as compared to spica cast group 9-10 weeks. TEN group A had a better out come than group B. Twelve patients in the spica cast group B had malunion. Postoperative superficial infection occurred in five patients and deep wound infection was observed in two patients in the TEN group A. Conclusion:Titanium elastic intramedullary nailing is an effective treatment of femoral shaft fractures in children